Carbon Nanotube Fibres and Yarns : Production, Properties and Applications in Smart Textiles - Miao, Menghe, editor 649050; ScienceDirect (Online service) 7722 (Oxford : Woodhead Publishing, 2020)
Carbon Nanotube Fibres and Yarns for Smart Textiles: Production, Properties and Applications in Smart Textiles explains the relevance of carbon nanotube science and provides new insights on this emerging, high-performance textile material. Particular emphasis is placed on applications in smart textiles and wearable electronics applications, such as flexible sensors, actuators and energy sources. This collection examines the state-of-the-art in carbon nanotube (CNT) research, providing guidance for anyone who is exploring problems where CNTs may provide design solutions. Finally, the book addresses advances in yarn spinning methods, yarn structures and properties. Drawing on his experience in the textile industry, the book's editor presents academic research in a way that is comprehensible and useful to materials scientists and engineers in practice.